1997
DOI: 10.1126/science.278.5335.141
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of CRM1 in Signal-Mediated Nuclear Protein Export

Abstract: Chromosome maintenance region 1 (CRM1), a protein that shares sequence similarities with the karyopherin beta family of proteins involved in nuclear import pathway, was shown to form a complex with the leucine-rich nuclear export signal (NES). This interaction was inhibited by leptomycin B, a drug that prevents the function of the CRM1 protein in yeast. To analyze the role of the CRM1-NES interaction in nuclear export, a transport assay based on semipermeabilized cells was developed. In this system, which reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
528
1
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 669 publications
(545 citation statements)
references
References 32 publications
14
528
1
2
Order By: Relevance
“…This double mutation similarly decreased the nuclear accumulation of GFPPyk2 700-841 induced by leptomycin B (LMB) (Fig. 2c) a toxin that blocks the nuclear export by competing with the binding of NES to CRM1 [39,40]. These findings strongly supported the idea that S 747 PT was a bona fide NTS involved in the control of GFP-Pyk2 700-841 nuclear import.…”
Section: Resultssupporting
confidence: 66%
“…This double mutation similarly decreased the nuclear accumulation of GFPPyk2 700-841 induced by leptomycin B (LMB) (Fig. 2c) a toxin that blocks the nuclear export by competing with the binding of NES to CRM1 [39,40]. These findings strongly supported the idea that S 747 PT was a bona fide NTS involved in the control of GFP-Pyk2 700-841 nuclear import.…”
Section: Resultssupporting
confidence: 66%
“…In analogy to shuttling cytoplasmic Rev mutants (Stauber et al, 1998a) inactivation of the NES resulted in nuclear accumulation of Rexp21IW18-GFP (compare Figures 2c and 3c). Recent reports demonstrated that the Rex and Rev export pathways are mediated by the export factor CRM1 and can be blocked by the drug leptomycin B (LMB) (Fornerod et al, 1997;Fukuda et al, 1997;Ossareh-Nazari et al, 1997;Stade et al, 1997;Wol et al, 1997). Thus, to verify the shuttling of Rexp21-GFP by an independent method, we blocked the CRM1 mediated nuclear export pathway using LMB.…”
Section: Rexp21-gfp Is Actively Shuttling Between the Nucleus And Thementioning
confidence: 99%
“…A leucine-rich nuclear export signal (NES), identi®ed between amino acids 79 and 99, is essential for nucleo-cytoplasmic tra cking and thus Rex function (Bogerd et al, 1996;Kim et al, 1996;Palmeri and Malim, 1996;Weichselbraun et al, 1992b). Factors reported to interact directly with the NES domain include the eukaryotic initiation factor 5A (eIF-5A) (Katahira et al, 1995) and the export factor CRM1 (Fornerod et al, 1997;Fukuda et al, 1997;Ossareh-Nazari et al, 1997;Stade et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation of the complex is likely to involve the exchange of GTP for GDP on the Ran moiety. It is unclear whether the returning importins carry a di erent cargo back to the cytoplasm, but nuclear export-speci®c importin b family members have been identi®ed that mediate the transport from the nucleus to the cytoplasm of, for example, tRNA (Arts et al, 1998a,b;Hellmuth et al, 1998;Kutay et al, 1998) or of proteins that contain a leucine-rich Nuclear Export Signal (NES); (Fornerod et al, 1997;Fukuda et al, 1997a;Neville et al, 1997;Ossareh-Nazari et al, 1997;Stade et al, 1997). Again, release of the export cargo at the cytoplasmic face of the nuclear pore is likely to involve the hydrolysis of GTP that is bound to the Ran component of the export complex (Bischo and Schlenstedt et al, 1997;Kehlenbach et al, 1999).…”
Section: Nuclear Transportmentioning
confidence: 99%